Self-employment and the local business cycle - Helena Svaleryd (Uppsala University, Department of Economics, 2013)
The business cycle is likely to be of importance for self-employment rates. When the economy is growing, business opportunities open up and encourage the set-up of new firms. In downturns, self-employment may be a way to avoid unemployment. The strength of these pull and push factors may depend on the amount of human capital a person has. The findings in this paper show that although the local business cycle is of minor importance for total self-employment rates in Sweden, there are heterogeneous effects across groups. People with higher human capital endowments are more likely to be pulled into self-employment, while those with lower human capital endowments are to a larger extent pushed into self-employment. This pattern is particularly strong for women.
urn:nbn:se:uu:diva-206313
Keywords: J21; J24; 330; self-employment; local business cycle; panel data